Book Development Based on Riau traditional Cultural With the Approach of Physics Concepts - Z, Fakhruddin; Sudrajad, Hendar (Proceedings of the UR International Conference on Educational Sciences, 2018)
The purpose of this study is to test the validity of Book based on Riau traditional cultural with the approach of Physics Concepts. The method of this research is Research and Development. It was conducted in the physics laboratory in physics education program at the university of Riau. Three physics educators to validate this book. The data is analyzed by a descriptive analysis to categorize the average score of the validity of Book based on Riau traditional cultural with the approach of Physics Concepts. Based on the analysis of research data, it is obtained an average score with high category, for all aspects that are rated at sub content , that is Traditional Cane Sugar Production, canoe runway, simple machine, Working Principles Of Traditional Hunting Tools, Physics Principles on Traditional rice process, Phycics concept in Traditional Music Tolls, Physics Concept in Tradisional Games and Phycics concept in Traditional Music Tolls (hit and blow up). It suggests Book based on Riau Traditional cultural with the approach of Physics Concepts valid so that it can be used as a reference for physics lessons